The perceptions of African women regarding natural menopause in Mamelodi, Tshwane district - Gloria N. Makuwa; Steppies R. Rikhotso; Fhumulani M. Mulaudzi (AOSIS, 2015)
Background: The majority of South African aging population are women, who spend late adulthood experiencing natural menopause. Despite the government spending billions of rand on different services for ageing women, menopausal challenges to African women still receive little attention. Objectives: The aim of the study was to explore and describe the perceptions of African women regarding natural menopause, in order to propose recommendations for health and social support systems for women in Mamelodi, Tshwane district. Method: A qualitative, exploratory, descriptive and contextual design was used to conduct the study. The population of the study consisted of menopausal women, between the ages 45 and 60 years or more, visiting the clinics for collection of chronic medication and othe rhealth assessment. Individual face-to-face interviews were conducted, using a semi-structured interview guide to collect data. Tesch's method of qualitative data analysis was used in the study. Results: The main theme that emerged from the study was 'attitude toward menopause', which was supported by cultural beliefs and experience. The African menopausal women expressed the importance of health support systems that will meet their needs within their context. Conclusion: Women's health programs and educational health information at facilities should include menopausal education to promote and improve health of all African menopausal women during their adulthood. There is a need to establish a women's health support group network within communities to share menopausal experiences with peers. The training and education curriculum of healthcare providers should include detailed menopause in order to provide comprehensive, congruent care.